The response of stream ecosystem properties to two size classes of herbivorous minnow species - Erika C. Martin (Ecology and Evolution, 2023)
Abstract Losses in freshwater fish diversity might produce a loss in important ecological services provided by fishes in particular habitats. An important gap in our understanding of ecosystem services by fishes is the influence of individuals from different size classes, which is predicted based on known ontogenetic shifts in metabolic demand and diet. I used 20 experimental stream mesocosms located at Konza Prairie Biological Station (KPBS), KS, USA, to assess the influence of fish size on ecosystem properties. Mesocosms included two macrohabitats: one riffle upstream from one pool filled with consistent pebble and gravel substrate. There were four experimental and one control treatment, each replicated four times (N = 20). I used two size classes of central stonerollers (Campostoma anomalum) and southern redbelly dace (Chrosomus erythrogaster). Five ecosystem properties were assessed: algal filament length (cm), benthic chlorophyll a (μg/cm2), benthic organic matter (g/m2), macroinvertebrate biomass (g/m2), and stream metabolism (g O2/m2/day−1). Size structure of fish populations affected some, but not all, ecosystem properties, and these effects were dependent upon species identity. Size structure of both species had effects on algal filament lengths where stonerollers of both size classes reduced algal filaments, but only small redbelly dace kept filaments short. A better understanding of the relationship between these prairie stream minnows and their small stream habitats could be useful to both predict changes in stream properties if species are lost (redbelly dace are a Species In Need of Conservation) or size structure shifts.